2017
DOI: 10.1111/fare.12258
|View full text |Cite
|
Sign up to set email alerts
|

Moods, Stressors, and Severity of Marital Conflict: A Daily Diary Study of Low‐Income Families

Abstract: Objective To examine links between negative moods, stressors, and daily marital conflict, and to test whether participation in a family‐strengthening program moderates those associations. Background Some family‐strengthening interventions have shown positive effects on low‐income married couples' relationships. Yet little is known about how these programs influence low‐income families' daily functioning. Method Families randomly assigned to the program participated in 10 weeks of relationship education. Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Perhaps, since fathers have historically been expected to be the “breadwinner” of the family and being a college student either diminishes this role altogether or makes it more difficult to fulfill, college student fathers experience more feelings of vulnerability due to their role contagion and spillover into their parent-child relationships compared to college student mothers. This finding is in line with previous literature that found money-related stress spills over into family relationships for fathers more than it does for mothers (McCormick et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Perhaps, since fathers have historically been expected to be the “breadwinner” of the family and being a college student either diminishes this role altogether or makes it more difficult to fulfill, college student fathers experience more feelings of vulnerability due to their role contagion and spillover into their parent-child relationships compared to college student mothers. This finding is in line with previous literature that found money-related stress spills over into family relationships for fathers more than it does for mothers (McCormick et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…The SHM intervention did include lessons and discussions focused on the importance of modeling positive interactions and constructive conflict for adolescent children. Given that wives in this study spent more time with their children (McCormick et al, 2017), such lessons about limiting spillover of negative interactions to more severe disagreements, particularly because of its effect on children, may have been most salient for women. In sum, this study provides some early descriptive evidence suggesting that a family strengthening intervention for low-income couples with adolescent children may influence the extent to which negative experiences in one domain of the marital relationship influence another domain.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, behavioral strategies taught within RE may be effective for some participants, but not as impactful for others. Yet, more global improvements to couple interaction and communication are also well-documented (e.g., Moore et al, 2018;Rauer et al, 2014;Rhoades, 2015;Williamson et al, 2016 / 1499 Merrilees, Choi, andCummings (2017) employed daily diary methods with 97 couples and found that RE-intervention couples reported weaker associations between daily mood and severity of marital disagreement. The researchers theorized that RE intervention influenced self-regulation of moods and stressors more generally, to the point that RE couples could better prohibit the spillover of daily stressors into marital disagreements.…”
Section: Relationship Education With Low-income Couplesmentioning
confidence: 99%